Bird Exploitation and Chicken Size in the Late Medieval and Early Modern Periods in Continental Croatia - Magdalena Kolenc; Aneta Piplica; Martina Čelhar; Tajana Trbojević Vukičević; Martina Đuras; Zoran Vrbanac; Kim Korpes (Quaternary)
The significance of birds in the medieval human diet has been greatly explored in Europe. However, there is a lack of systematic analysis of data from Croatia. Avian remains dated to the Late Medieval and Early Modern Periods from five archaeological sites in continental Croatia underwent skeletal and taxonomic analysis. Age groups were determined and sex identification was conducted using visual and X-ray diagnostics. Chicken bone measurements were taken, and the logarithmic size index (LSI) technique was performed. Statistical analysis was applied to explore differences between sites. A total of 694 avian remains were studied, revealing 10 species/genera. Avian remains ranged from 8.88% to 20.32% across sites, with the highest percentage found at the urban site BAN. Hens outnumbered cockerels across all sites, with adult chickens prevailing over immature and subadult ones. Chicken sizes were generally consistent across sites, except for castle MIL, where a larger breed was identified. Cockerels tended to be larger than hens, except for one small-sized spurred specimen. To conclude, bird exploitation complemented the use of other animals in diets. Chickens were vital for eggs and meat, with monasteries excelling in bird husbandry over castles. Inhabitants of urban areas mainly consumed bird meat. Castles showed high status through game and imported birds. The aim of this article was to fill in the gap of information regarding the exploitation and consumption of birds at Croatian sites during the Late Medieval and Early Modern Periods.